WOMEN AND MARRIAGE: AN ANALYSIS COMPARATIV LITERATURE ON THE NOVEL INDONESIA, ENGLAND, AND AMERICA - Syahril, Syahril (Ar Raniry : International Journal of Islamic Studies, 2017)
A novel can represent reality. Thus, a character in a novel with his or her complexity, might be a portrait or a representation of a real person. This article discusses representations or images of women in three novels from three different social background. They are Kalau Tak Untung (Selasih, Indonesia), Far From The Madding Crowd (Thomas Hardy, England), and The Great Gatsby (F. Scott Fitzgerald, United States). All of these three novels represent women in both positive and negative images. The positive images are: independent, hard working, rebellious, and futuristic (in thinking). Meanwhile, the negative images are reckless, naïve, materialistic, seductive, unfaithful, egoist and passive. The three novels show some facts. The first is that women will work hard when they are in an unpleasant situation, particularly when they need money. In this situation they will not mind doing man’s job. The second similarity is that woman with good education seems to have better behavior than those who lack education. The third fact is that there are some women who value their happiness by the wealth they can get.